Potential impact of trips-plus provisions on Malaysia’s domestic pharmaceutical industry - Idris, Rafiq; Alavi, Rokiah; Mohd Amin, Ruzita; Mat Ghani, Gairuzazmi (Science International, 2019)
Trans-Pacific Partnership Agreement (TPPA) which is now known as the Comprehensive and Progressive Agreement on Trans Pacific Partnership (CP-TPP) opens door of opportunities as well as challenges to Malaysia. The agreement has become subject of heated debate in Malaysia as well as other countries due to the reason that it may bring some new elements which are not in the other earlier Free Trade Agreements (FTA) on which Malaysia has signed. One of the key concern is the possibility of including WTO-Plus commitments in the agreement which is TRIPS-Plus element which may affect access to medicine and the local pharmaceutical industry. This study focuses on one issue that is on the potential impact of TRIPS-Plus provisions in the intellectual property chapter on Malaysia’s pharmaceutical domestic industry sales. In assessing the potential impact of the TPPA on Malaysia’s pharmaceutical industry, simulation exercise using Model of Impact Changes in Intellectual Property Rights have been undertaken. The finding of the study indicates that domestic pharmaceutical industry sales may drop if data exclusivity, patent term restoration and patent linkage is being implemented.